Analisis dan Pemanfaatan Unsur Belerang dan Salinitas Lumpur Bledug Kuwu di Desa Kuwu, Kecamatan Kradenan, Kabupaten Grobongan, Jawa Tengah - Sepridawati Siregar; Nora Idiawati Siregar (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2016)
This study was conducted to determine the levels of elemental sulfur and salinity of the mud Bledug Kuwu. The research area has a subsurface lithology bedding rock mud, sand stone and rocks submerged in saltwater, brackish water and sea water. Bledug Kuwu is a phenomenon of volcanic mud. Around Kuwu found several indications of an ancient sea that connect up to the east, that is to Cepu and westward to the region Boja and Cirebon. Judging from geological formations, estimated Kuwu to Cepu was once the sea. The ancient sea stretching from Bledug Kuwu region to the southwest that is to Sangiran and also to Boyolali. Bledug Kuwu mud has a high sulfur and salt contents, evidenced from the results of laboratory analysis where the average concentration of sulfur 62,883 x102 mg/Kg with UV-vis spectrophotometry method and the average of salinity 57,15 mg/L by the Conductometry method. From the analysis, Bledug Kuwu mud can be used for tourism and an additional income for the local community. the mud of Bledug kuwu has high content of sulfur can be used as a treatment especially for skin diseases and salinity can be used for making salt.